Multidisciplinary approach to children with sinonasal tumors: A review - Norhafiza Mat Lazim; Baharudin Abdullah (Wiley, 2019)
Abstract Sinonasal tumors in children are rare and difficult to manage. These tumors can be broadly categorized into congenital or acquired and benign or malignant. The tumors mainly arise from the mucosa, cartilage, or bone of the nasal cavity and may occupy areas of the nasal septum, turbinates, osteomeatal complex, sinuses, and nasopharynx. The management of pediatric sinonasal tumors is challenging, especially in cases of malignancy. Malignant tumors pose a treatment dilemma because most such tumors tend to be aggressive and carry a poor prognosis. Multiple complications associated with the primary disease or treatment may occur, and such complications need to be fully addressed to provide optimal care. In most cases, a multidisciplinary team approach will offer the best possible outcome for children with sinonasal tumors.